PROFIL PENGAJUAN SOAL KONTEKSTUAL DITINJAU DARI GAYA BELAJAR VARK - SITI NURIYATIN (JEDMA Jurnal Edukasi Matematika, 2020)
This study used a qualitative researched that aimed to describe profile of students’ ability in filing of problems (problem posing) contextual math problems from VARK’s learning style. This study is held in the class VIII-C of MTs Ma’arif NU Ngaban, Tanggulangin. The participants of this study is 4 students which consist of 1 student with visual learning style, 1 student with aural learning style, 1 student with read/write learning style and 1 student with kinesthetic learning style. Instruments used questionnaire sheets, test question sheets, and interview guidelines. The results showed that each subject can understanding information. At the stage of implementing completion plan and the stage of re-checking, visual, read / write, and kinesthetic subject can implement the completion plan as planned.